2021
DOI: 10.1101/2021.02.24.432768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding the brain state-dependent relationship between pupil dynamics and resting state fMRI signal fluctuation

Abstract: Pupil dynamics serve as a physiological indicator of cognitive processes and arousal states of the brain across a diverse range of behavioral experiments. Pupil diameter changes reflect brain state fluctuations driven by neuromodulatory systems. Resting state fMRI (rs-fMRI) has been used to identify global patterns of neuronal correlation with pupil diameter changes, however, the linkage between distinct brain state-dependent activation patterns of neuromodulatory nuclei with pupil dynamics remains to be explo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The PCA time courses were variance normalized before the optimization of linear regression and GRU weights. The functional and anatomical data are available online (84).…”
Section: Fmri Acquisition and Preprocessingmentioning
confidence: 99%
“…The PCA time courses were variance normalized before the optimization of linear regression and GRU weights. The functional and anatomical data are available online (84).…”
Section: Fmri Acquisition and Preprocessingmentioning
confidence: 99%
“…As head-fixed mice frequently sleep with their eyes open (Karimi Abadchi et al, 2020;Turner et al, 2020;Yuzgec et al, 2018), it has been observed that pupil diameter is lower during sleep and can be used detect sleep events minute-to-minute timescale (Karimi Abadchi et al, 2020;Yuzgec et al, 2018). Changes in pupil diameter are tightly coupled with BOLD fMRI signals seen neuromodulatory centers (Pais-Roldan et al, 2020;Sobczak et al, 2021). In addition to noradrenergic effects on neurons, noradrenergic input from the locus coeruleus causes vasoconstriction of cortical arteries (Bekar et al, 2012), coupling cortical hemodynamics to arousal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its effects on neurons, noradrenergic input from the LC causes vasoconstriction of cortical arteries (Bekar et al, 2012). LC activity and noradrenergic tone provides a potential mechanism for coupling arousal to cortical hemodynamics (Pisauro et al, 2016), as changes in pupil diameter are also correlated with blood-oxygen-level-dependent (BOLD) signals seen in neuromodulatory centers during functional magnetic resonance imaging (fMRI) (Pais-Roldan et al, 2020;Sobczak et al, 2021). Both head-fixed and freely behaving mice frequently sleep with their eyes open (Karimi Abadchi et al, 2020;Senzai and Scanziani, 2022;Turner et al, 2020;Yuzgec et al, 2018).…”
Section: Introduction (634 Words)mentioning
confidence: 99%